Pengaruh Model Pembelajaran Inquiry Based Learning Terhadap Hasil Belajar Matematika Siswa SMP - Nur Baeti; Mikrayanti Mikrayanti (Program Studi Pendidikan Matematika, 2021)
This study aims to determine the effect of the Inquiry Based Learning learning model on the mathematics learning outcomes of junior high school students. This research is included in the quasi-experimental research. The design of this study used a control group pretest and posttest design. This study used one experimental class and one control class. The experimental class was given learning treatment with Inquiry Based Learning learning model, while the control class was given learning treatment using conventional learning with discussion, lecture and question and answer methods. The research population was all eighth grade students of SMP Negeri 11 Bima City. The sampling technique used was cluster random sampling, in order to obtain class VIII A as the experimental class and VIII C as the control class. The data collection technique used a description test. Hypothesis testing using independent sample t-test. The results of this study indicate that the use of the Inquiry Based Learning learning model has an effect on students' mathematics learning outcomes at SMP Negeri 11 Bima City.